Dampak Reviktimisasi Terhadap Penyintas Kekerasan Seksual dalam Proses Penyidikan - David Brain Siregar; Juanrico Alfaromona Sumarezs Titahelu; Denny Latumaerissa (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: The Police, as the primary institution in the criminal justice system responsible for handling victims of sexual harassment, plays a central role in ensuring the rights of citizens. These rights include accessibility to the criminal justice process and equality before the law. However, the reality of the investigative process often neglects the rights of the victims in formal legal practices, leading to re-victimization during the formal process. The ramifications of legal practices resulting in re-victimization during the formal legal process have widespread impacts on the victims and the community at large. The purpose of this research is to identify and analyze the impact of re-victimization on victims of sexual violence during the investigation process. The research method employed is Normative research, which involves studying available literature materials. The approach to the issue includes legislative approaches, conceptual approaches, and case-based approaches. The collection of legal materials is then analyzed qualitatively. The study reveals that when victims of sexual violence are subjected to re-victimization during the criminal justice process, it has negative psychological effects on them. The term